The influence of ligands in Pinhey phenylation reactions using lead(IV) tetracarboxylates - Moloney, M; Paul, DR; Prottey, S; Thompson, R; Wright, E (1997)
Lead(IV) tetracarboxylates, prepared from achiral and chiral carboxylic acids, have been shown to undergo metal-metal exchange with phenylboronic acid, and the phenyllead(IV) carboxylates thus generated in situ can be used for Pinhey phenylation reactions. Although the yields of these reactions are generally moderate to good, only low levels of asymmetric induction at best were observed. Possible reasons for this lack of enantioselectivity are discussed.